2019
DOI: 10.1523/jneurosci.1888-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Fidgetin Improves Regeneration of Injured Axons by a Microtubule-Based Mechanism

Abstract: Fidgetin is a microtubule-severing protein that pares back the labile domains of microtubules in the axon. Experimental depletion of fidgetin results in elongation of the labile domains of microtubules and faster axonal growth. To test whether fidgetin knockdown assists axonal regeneration, we plated dissociated adult rat DRGs transduced using AAV5-shRNA-fidgetin on a laminin substrate with spots of aggrecan, a growth-inhibitory chondroitin sulfate proteoglycan. This cell culture assay mimics the glial scar fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 55 publications
2
38
0
Order By: Relevance
“…Studies have indicated that microtubule dynamics are largely regulated by microtubule-severing proteins [9,32,33]. Moreover, microtubule-severing proteins have been shown to be essential for neurite outgrowth and axon branching [34][35][36][37]. This led us to hypothesize that microtubule-severing proteins might be vital players in the neurite outgrowth directed by the RhoA signaling pathway.…”
Section: The Rhoa Signaling Pathway Inhibits Spastin and P60-kataninmentioning
confidence: 99%
“…Studies have indicated that microtubule dynamics are largely regulated by microtubule-severing proteins [9,32,33]. Moreover, microtubule-severing proteins have been shown to be essential for neurite outgrowth and axon branching [34][35][36][37]. This led us to hypothesize that microtubule-severing proteins might be vital players in the neurite outgrowth directed by the RhoA signaling pathway.…”
Section: The Rhoa Signaling Pathway Inhibits Spastin and P60-kataninmentioning
confidence: 99%
“…A number of molecules affect microtubule dynamics by binding to them and having the ability to sever the microtubules, spastin atlastin fidgetin and katanin are examples. The level of these molecules is critical: in Drosophila if levels of spastin and atlastin are too high or too low regeneration fails [107], and fidgetin is a regeneration inhibitor [89]. Kinesins are generally thought of as transport molecules, but some can also affect microtubule dynamics.…”
Section: The Axonal Cytoskeletonmentioning
confidence: 99%
“…It serves as the major track for vesicular transport through the axon shaft, provides structural support to the axon, and, in the distal region of the axon, polymerizing MTs play a critical role in promoting axon elongation and in steering the growth cone in response to environmental cues [1,2]. Given its role in regulating axonal growth, targeting the MT cytoskeleton to enhance axon regeneration after nerve injury has been proposed as a potential therapeutic strategy [3][4][5][6][7][8][9][10][11]. This proposition is supported by studies demonstrating that modulation of MT dynamics in the axon can promote regeneration and attenuate degeneration: for example, multiple studies have found that low doses of MT stabilizing drugs (taxol and epothilones) promote axon regeneration and improve recovery of locomotor function after spinal cord injury (SCI) in rats [5][6][7]11].…”
Section: Introductionmentioning
confidence: 99%
“…This proposition is supported by studies demonstrating that modulation of MT dynamics in the axon can promote regeneration and attenuate degeneration: for example, multiple studies have found that low doses of MT stabilizing drugs (taxol and epothilones) promote axon regeneration and improve recovery of locomotor function after spinal cord injury (SCI) in rats [5][6][7]11]. Increasing the density of dynamic MTs in the axon by knocking down the MT severing enzyme fidgetin was also shown to promote axon regeneration after dorsal root crush in rats [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation